Weaving and Unweaving the Web: Feudal Rites from the Marriage Rites and Culture of The Scholars - Chen, Yuhan (International Journal of Social Sciences and Public Administration, 2024)
Through the satirical portrayal and in-depth analysis of the marital status of different character images under the eight-part essay system, The Scholars discovers that the feudal rites of the ancient society are implied behind the marriage rituals. Through the scene depiction and in-depth exploration of more than a dozen weddings in The Scholars, this paper finds that the wedding scenes in the novel are all significant in enhancing the artistic features of the novel as well as exposing the reality and revealing the self-contradictory and decaying side of China’s feudal and ritualistic society. At the same time, it also reveals that the author of The History of Confucianism, in his efforts to explore the culture of marriage etiquette and customs, shows his ambivalence in worrying about the status and wanting to make a change to it, but is unable to do anything about it because of his attachment to the culture of etiquette and customs.